2008
DOI: 10.1007/s00586-008-0709-7
|View full text |Cite
|
Sign up to set email alerts
|

Persons with recurrent low back pain exhibit a rigid postural control strategy

Abstract: Persons with recurrent low back pain (LBP) have been observed to have altered proprioceptive postural control. These patients seem to adopt a body and trunk stiffening strategy and rely more on ankle proprioception to control their posture during quiet upright standing. The aim of this study is to determine the effect of changing postural condition (stable and unstable support surface) on postural stability and proprioceptive postural control strategy in persons with recurrent LBP. Postural sway characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
251
9
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 247 publications
(283 citation statements)
references
References 32 publications
18
251
9
5
Order By: Relevance
“…Although the knowledge surrounding proprioception is relatively limited because it is such a complex function, several studies have found that proprioceptive deficits in individuals with LBP might contribute to a lack of stability [8,33,34]. Another explanation for decreased balance performance in LBP subjects might be altered muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…Although the knowledge surrounding proprioception is relatively limited because it is such a complex function, several studies have found that proprioceptive deficits in individuals with LBP might contribute to a lack of stability [8,33,34]. Another explanation for decreased balance performance in LBP subjects might be altered muscle function.…”
Section: Discussionmentioning
confidence: 99%
“…1): transmuscular surgery + physiotherapy (n = 6), transmuscular surgery + usual care (n = 6), paramedian surgery + physiotherapy (n = 6), and paramedian surgery + usual care (n = 7). These groups were clustered by a mixed group design because power analysis (Brumagne et al, 2008;Claeys et al, 2011Claeys et al, , 2012Claeys et al, , 2015Janssens et al, 2015) revealed a sample size of 11 participants to provide adequate power (0.80 with a two-tailed alpha level of 0.05) to detect a clinically relevant difference in center of pressure displacement on unstable support surface (our primary outcome measure with smallest effect size). First, they were randomly allocated (blinded by computer algorithm) for surgical approach into a transmuscular group (n = 12; 7 women/5 men) and paramedian group (n = 13; 7 women/6 men).…”
Section: Participantsmentioning
confidence: 99%
“…The amount of this center of pressure displacement represents the extent to which an individual makes use of the proprioceptive signals of the vibrated muscles to maintain the upright posture. Muscle vibrators (Maxon motors, Switzerland) were applied bilaterally over the triceps surae ('ankle') muscles and lumbar paraspinal ('back') muscles, as studied previously (Brumagne et al, 2008;Claeys et al, 2011Claeys et al, , 2012Claeys et al, , 2015Janssens et al, 2015). Participants were instructed to stand barefoot on the force plate, with their arms relaxed along the body and occluded vision.…”
Section: Primary Outcome Measuresmentioning
confidence: 99%
See 2 more Smart Citations